Zebrafish housing: the recirculating and cost-effective open design aquaria system - Raduan, Siti Zaleha; Ahmed, Qamar Uddin; Ahmad Rusmili, Muhamad Rusdi; Mohmad Sabere, Awis Sukarni; Haris @ Harith, Muhammad Salahuddin; Shaikh, Mohd Farooq; Wan Sulaiman, Wan Azizi; Zulkifli, Nor Asyikin; Mahmood, Muhammad Hamdi (UPM Press, 2024)
The zebrafish’s ease of care and high reproductive rate have made them a popular animal model. It is routinely kept and maintained in commercial aquariums. However, the expense of a particular system was prohibitive for researchers with limited budgets or who worked in universities without zebrafish-rearing facilities. Thus, a simple custom-made aquaria system was developed. The recirculating opendesign aquaria system was cost-effective and may frequently be improved. This study has developed a distinctive aquaria system that can tackle the issues related to expanding research based on zebrafish